Psychological Conflicts in Bystander Cardiopulmonary Resuscitation for Out-of-HospitalCardiac-Arrest (International Journal of First Aid Education)
Aim: Bystander cardiopulmonary resuscitation (CPR) plays an important role in saving the lives of out-of-hospital cardiac arrest (OHCA) patients. Although many factors have been suggested as barriers to performing CPR, the psychological processes and factors related to bystander CPR have not been sufficiently evaluated. The aim of this study was to analyze and describe the psychological processes in bystander CPR through detailed interviews. Method: We planned a mixed-method study and qualitative research was conducted by means of semistructured interviews of bystanders who had encountered OHCA as the first step. Data from the interviews regarding the “CPR process” and “factors related to the CPR process” were analyzed inductively. Results: We assessed 16 OHCA cases encountered by 14 bystanders. Five categories, comprising “motives for lifesaving,” “facilitators for CPR,” “barriers for CPR,” “knowledge and experience,” and “OHCA situation and its circumstances,” and 19 concepts were generated. Although all bystanders intended to save the individual’s life when they encountered an OHCA, all of them had experienced psychological conflict between whether they should perform CPR or not. Implication: Therefore, as countermeasures for the reported conflicts, CPR training courses including preparation of psychological stress, despatcher instruction over the phone, and AED’s voice advice, will be important to encourage bystanders to perform CPR in real OHCA settings.